Strategi Kinerja Pegawai: Disiplin Kerja dan Kompetensi di SAMSAT Kabupaten Sidenreng Rappang - Renata, Tiara; Dinsar, Arfandy; Angka, Andi FItri Sugi; Hasan, Hamida (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to find out and find the relationship between the disciplinary and compensation variables on employee performance at the One-Stop Single Administration System Joint Office (SAMSAT) in Sidenreng Rappang Regency, both partially and simultaneously.The analytical method used in this study is Multiple Linear Regression Analysis, Validity Test, Reliability Test, Partial Test (t test), Simultaneous test (F test) and Coefficient of Determination Test (R2 test) with a sample of 43 respondents.The results showed that work discipline (X1) had a positive and partially significant effect on the performance (Y) of employees at the One-Stop Single Administration System Joint Office (SAMSAT) in Sidenreng Rappang Regency, with a t-count value of 3.278 > ttable 2.021 and a significant value of 0.002 <0.05. Competence (X2) has a positive and partially significant effect on the performance (Y) of employees at the One-Stop Single Administration System Joint Office (SAMSAT) Sidenreng Rappang Regency with a tcount value of 3.057 > ttable 2.021 and a significant value of 0.004 <0.05. Each variable has a positive and significant simultaneous effect on the performance of employees at the Joint Office of the One-Stop Single Administration System (SAMSAT) in Sidenreng Rappang Regency with an Fcount of 100.533 > Ftable 3.23 and a significant value of 0.000 <0.05.